A new method for determining the P-V-T properties of high-density H2O using NMR: Results at 1.4-4.0 GPa and 700-1100 degrees C - Withers, A; Kohn, S; Brooker, R; Wood, B (2000)
A new method for determining the density of H2O at high pressures and temperatures has been developed using 1H magic angle spinning NMR. Powdered γ-Al2O3 was recrystallised in the piston-cylinder apparatus under hydrothermal conditions to form corundum containing submicroscopic fluid inclusions. After quenching, 1H NMR spectra of the included water were measured at room temperature with the result that the shift relative to H2O at 25°C and 1 bar was found to be dependent on the predicted density of the trapped fluid. The shifts appear to be related to changes in the bulk magnetic susceptibility of water that increases linearly with density. The linear relationship between density and measured shift was calibrated using two measurements of the depression of freezing point in high-density water and enabled us to determine densities in the range 1.0-1.25 g cm-3. Therefore, the technique is complementary to those based on homogenisation of two phase (liquid-vapour) fluid inclusions; the latter techniques are only applicable where water density is <1 g cm-3. Because of the importance of high-density fluids under subduction zone conditions the density of water was determined using the new methodology at 1.4-4.0 GPa and 700-1100°C to test the available equations of state. We find that for the equations of state of Brodholt and Wood, Saul and Wagner, and Pitzer and Sterner the average difference between the calculated and measured values of density is about 1%, less than our estimate of the experimental error. Other widely used equations of state predict densities that are not consistent with our data. For example, those of Saxena and Fei and Holland and Powell predict densities, which are too high by an average of 7.6% and 3.8%, respectively, over the pressure and temperature range studied here. Copyright (C) 2000 Elsevier Science Ltd.